Penegakan Hukum Terhadap Pelanggaran Izin Trayekd di Kabupaten Manggarai Tengah - Mariano Roberto Solsepa; Ida Ayu Putu Widiati; I Putu Gede Seputra (Jurnal Konstruksi Hukum, 2021)
The transportation sector has an important role in increasing the mobility of citizens, so the task of the Central Manggarai Regency Transportation Agency is to issue permits for carrying out transportation of people on routes in the form of public transport permits and curbing public transport that does not have a route permit. The method used in this research is empirical legal research. From the results of the study there are still many route permit violations in Central Manggarai Regency. This study aims to determine the effectiveness and law enforcement of Manggarai Tengah District Regulation No.18 of 2011 concerning Route Licensing Retribution. To find out the effectiveness and enforcement of Regional Regulation No.18 of 2011, the theory used is legal effectiveness. Regulations for Route Permits in Central Manggarai Regency can be said to be ineffective given the many violations of public transport route permits. Efforts made in enforcing public transportation that do not have a route permit in Central Manggarai Regency are socializing to owners of public transport services about the importance of public transport route permits.